Efficacy of Intravenous Immunoglobulins and Other Immunotherapies in Neurological Disorders and Immunological Mechanisms Involved - Angel Justiz-Vaillant; Sachin Soodeen; Odalis Asin-Milan; Julio Morales-Esquivel; Rodolfo Arozarena-Fundora (Immuno, 2025)
This review aims to explore the role of immunotherapeutic strategies—primarily intravenous immunoglobulin (IVIG), plasma exchange (PLEX), and selected immunomodulatory agents—in the treatment of neurological and psychiatric disorders with suspected or confirmed autoimmune mechanisms. A central focus is placed on understanding the immunopathology of these conditions through the identification and characterization of disease-associated autoantibodies. Disorders such as autoimmune encephalitis, myasthenia gravis, limbic epilepsy, neuropsychiatric systemic lupus erythematosus (NPSLE), and certain forms of schizophrenia have shown clinical responses to immunotherapy, suggesting an underlying autoimmune basis in a subset of patients. The review also highlights the diagnostic relevance of detecting autoantibodies targeting neuronal receptors, such as NMDA and AMPA receptors, or neuromuscular junction components, as biomarkers that guide therapeutic decisions. Furthermore, we synthesize findings from published randomized controlled trials (RCTs) that have validated the efficacy of IVIG and PLEX in specific diseases, such as Guillain–Barré syndrome, and myasthenia gravis. Emerging clinical evidence supports expanding these treatments to other conditions where autoimmunity is implicated. By integrating immunological insights with clinical trial data, this review offers a comprehensive perspective on how immunotherapies may be tailored to target autoimmune contributors to neuropsychiatric disease.